2016
DOI: 10.1063/1.4953040
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Proper use of broken-symmetry calculations in antiferromagnetic polyradicals

Abstract: Broken symmetry approach to density functional calculation of zero field splittings including anisotropic exchange interactions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…(2) and (3). From a formal point of view, arguments both in favor [39,41] and against spin projection [42][43][44] have been presented. Studies in the literature [45,46] have revealed that the agreement with experiment is better for the unprojected formula as long as hybrid functionals are employed.…”
Section: Broken-symmetry Approach To Spin Couplingmentioning
confidence: 99%
“…(2) and (3). From a formal point of view, arguments both in favor [39,41] and against spin projection [42][43][44] have been presented. Studies in the literature [45,46] have revealed that the agreement with experiment is better for the unprojected formula as long as hybrid functionals are employed.…”
Section: Broken-symmetry Approach To Spin Couplingmentioning
confidence: 99%
“…Systematic comparisons between our predictions and the behavior of UDFT-B3LYP calculations will be presented for six series of compounds in section , confirming the validity of our model. Moreover the method enables one to predict whether the symmetry breaking may also concern deeper occupied MOs, for instance the HOMO-1 and the LUMO+1 orbitals, as has been observed in very long polyacenes and in regular fused rhomboidal polyacenes . Some comparative UHF results will be presented in section .…”
Section: Introductionmentioning
confidence: 98%
“…Moreover the method enables one to predict whether the symmetry breaking may also concern deeper occupied MOs, for instance the HOMO-1 and the LUMO+1 orbitals, as has been observed in very long polyacenes and in regular fused rhomboidal polyacenes. 54 Some comparative UHF results will be presented in section 3.3.…”
Section: Introductionmentioning
confidence: 99%
“…Broken-Symmetry DFT method (BS-DFT) [49][50][51][52] is an affordable method to describe open-shell singlets within a monodeterminantal scenario. This method, widely used for the treatment of diradical systems, 39,[53][54][55][56][57][58] introduces the breakdown of the spatial and spin symmetry in decoupled alpha and beta spin-orbital contributions. Then, the splitting of the spin contribution and the frontier orbital mixing introduces the correction of the static correlation.…”
Section: A Broken-symmetry Dftmentioning
confidence: 99%